NICER-NuSTAR Observations of the Neutron Star Low-mass X-Ray Binary 4U 1735-44 - Ludlam, R. M.; Cackett, E. M.; Garcia, Javier; Miller, J. M.; Bult, P. M.; Strohmayer, T. E.; Guillot, S.; Jaisawal, G. K.; Malacaria, C.; Fabian, A. C.; Markwardt, C. B. (Astrophysical Journal, 2020)
We report on the first simultaneous Neutron Star Interior Composition Explore (NICER) and Nuclear Spectroscopic Telescope Array (NuSTAR) observations of the neutron star (NS) low-mass X-ray binary 4U 1735-44, obtained in 2018 August. The source was at a luminosity of similar to 1.8 (D/5.6 kpc)(2) x 10(37) erg s(-1) in the 0.4-30 keV band. We account for the continuum emission with two different continuum descriptions that have been used to model the source previously. Despite the choice in continuum model, the combined passband reveals a broad Fe K line indicative of reflection in the spectrum. In order to account for the reflection spectrum we utilize a modified version of the reflection model relxill that is tailored for thermal emission from accreting NSs. Alternatively, we also use the reflection convolution model of rfxconv to model the reflected emission that would arise from a Comptonized thermal component for comparison. We determine that the innermost region of the accretion disk extends close to the innermost stable circular orbit (R-ISCO) at the 90% confidence level regardless of reflection model. Moreover, the current flux calibration of NICER is within 5% of the NuSTAR/FPMA(B).
CRIS-Team WoS Importer:2020-06-16